2005
DOI: 10.3748/wjg.v11.i6.867
|View full text |Cite
|
Sign up to set email alerts
|

YMDD mutations in patients with chronic hepatitis B untreated with antiviral medicines

Abstract: Wild mutant strains in HBV and their incidence rate have no significant difference between familial aggregation and non-familial aggregation. It may have no significant relationship between YMDD mutations and pre-c-zone mutations. HBV DNA level may not have a positive correlation with YMDD mutations. LAM is clinically effective for CHB patients with YMDD mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 19 publications
2
56
3
Order By: Relevance
“…The rate of YMDD mutations in patients after one year of LAM therapy was 14-32% (7,8,10,16,20). However, the rate of YMDD mutation after one year LAM therapy of the present study was 12.12%, which is slightly lower than a previous study (15). Allen (8) classified YMDD mutations into two categories: rtM204V + rtL180M and rtM204I, and the study suggested that rtM204V and rtL180M do not occur alone.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…The rate of YMDD mutations in patients after one year of LAM therapy was 14-32% (7,8,10,16,20). However, the rate of YMDD mutation after one year LAM therapy of the present study was 12.12%, which is slightly lower than a previous study (15). Allen (8) classified YMDD mutations into two categories: rtM204V + rtL180M and rtM204I, and the study suggested that rtM204V and rtL180M do not occur alone.…”
Section: Discussioncontrasting
confidence: 53%
“…This motif, which is localized in the polymerase structural region C area, is the combing and functioning site of Lamivudine (a nucleoside antiviral). Lamivudine-resistant HBV strains with YMDD mutations have been implemented in the failure of chronic hepatitis B treatment (15). It has been reported that the seminested PCR products of the DNA polymerase gene exhibit intergenotypic divergence of ≥4%, which is in accordance (5,(14)(15)(16), and the effect of the genotype on LAM therapy is different (5,17,18).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Lamivudine has revolutionized the treatment of chronic hepatitis B. Lamivudine-resistant mutations in the YMDD motif of polymerase gene were detected in lamivudine treated and untreated patients with chronic hepatitis B [14,[17][18][19] . Clinical breakthrough was observed 2 wk-7 mo after the emergence of YMDD mutations [8][9][10] , causing considerable morbidity and mortality in those patients [20][21][22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…Several factors may contribute such as noncompliance, inefficient conversion from the prodrug to its active metabolite, inadequate phosphorylation within the hepatocytes or underdosing of the dr ug. Some patients failing to respond initially to treatment may already harbour a resistant mutant prior to the start of therapy [90,91] . Underdosing is particularly an issue with adefovir treatment as the 10 mg dose was chosen for safety reasons.…”
Section: Management Of Treatment Failures To Nucleos(t)ide Analoguesmentioning
confidence: 99%